The impact of leadership learning on work locus of control - Salman, Dlofan; Nori , Range (Humanities Journal of University of Zakho, 2024)
The study aimed to investigate the impact of leadership learning practices on the work locus of control among heads of departments at public universities in the Kurdistan Region-Iraq. More precisely, the study concentrated on investigating the impact of selected leadership learning practices; self-managed, practice-based, and formal learning practices on work locus of control. Data were collected from 207 heads of departments from different public universities in the Kurdistan Region-Iraq. A self-administered questionnaire of three parts was sent online to the participants to collect the primary data from the sample under the research. Descriptive and inferential statistics were utilized to analyze the collected data and test the research hypotheses using SPSS (25.0). The empirical results showed a positive relationship between leadership learning practices and locus of control. The Pearson correlation analysis revealed that all three leadership learning practices (self-managed, practice-based, and formal learning) were significantly related to the locus of control. The results of regression analysis supported these findings and revealed that leadership learning practices collectively explained 24% of the variance in the locus of control. The practice-based learning and formal learning practices were found to have the strongest positive impact on locus of control, while self-managed learning had a weak and insignificant impact. Hence, it can be said that these results assert the importance of leadership learning practices in promoting individuals’ locus of control. It is also suggested that investing in formal and practice-based leadership learning programs may positively influence the individual’s locus of control, which can have significant implications for personal and professional development. The findings indicate a positive relationship between leadership learning practices and locus of control. The Pearson correlation analysis revealed that all three leadership learning practices (self-managed, practice-based, and formal learning) were significantly related to locus of control. The results of regression analysis supported these findings and revealed that the three sub-dimensions of leadership learning practices significantly predict the locus of control, explaining 24% of the total variance. The practice-based learning and formal learning practices were found to have the strongest positive impact on locus of control, while self-managed learning had a weak and insignificant impact. Hence, it can be said that these results assert the importance of leadership learning practices in promoting individuals’ locus of control. The study also suggests that investing in formal and practice-based leadership learning programs may positively influence the individual’s locus of control, which can have significant implications for personal and professional development.